University students’ global citizenship development through long-term study abroad - Suzuki, Ayako (Journal of English as a lingua franca, 2022)
Study abroad (SA) is one of the popular ways for universities to develop their students as global citizens because the experience of sojourning is believed to be able to improve the students’ language skills of English as an international lingua franca as well as global awareness. This paper investigates whether SA can contribute towards the development of global citizenship, focusing on a group of Japanese students’ perceptions of English. This study reveals that SA may need some interventions in order to fulfill the expected role.